Analisis Determinan Struktur Modal : Studi Indonesia - Atika Wardati Hubbi; Debbi Chyntia Ovami (Politeknik Ganesha Medan, 2023)
This study aims to examine the effect of asset structure, profitability and liquidity on the capital structure of metal and similar companies listed on the Indonesia Stock Exchange in 2019-2021. Determination of the sample using the purposive sampling method, samples obtained by 14 metal companies and the like in the 2019-2021 timeframe so that 42 observations were obtained. The data used is secondary data and the data analysis technique used is multiple linear regression method by conducting a series of assumption tests to ensure the feasibility of the data. Data processing used in this study uses panel data regression with the help of Eviews software version 10. The results of this study indicate that asset structure has a positive and significant effect on capital structure, profitability has a positive and significant effect on capital structure, and liquidity has a negative and significant effect on capital structure. capital. Based on the results of the simultaneous test (Test F) shows that all independent variables simultaneously or jointly affect the dependent variable.